Pengaruh Konsentrasi Tembaga dan Rapat Arus terhadap Morfologi Endapan Elektrodeposisi Tembaga - Wahyudi, Soleh; Soepriyanto, Syoni; Mubarok, Mohammad Zaki; Sutarno, Sutarno (Al-Kimia, 2019)
Copper deposits have been obtained by the electrolysis method using copper sulfate and sulfuric acid. The effect of copper concentration and current density on the surface morphology of copper deposits and current efficiency have been studied. The variation of copper concentration is 0.04 M and 0.8 M and the variation of current density is 2-8 A/dm2. The copper deposits will be photographed macro, weighed and characterized by Scanning Electron Microscope (SEM) to determine the surface morphology of deposits and Energy-Dispersive X-ray spectroscopy (EDX) to determine the chemical composition of deposits. The surface morphology of copper deposits in the form of compact and without nodules was reached at copper concentration is 0.8 M and the current density is 2 A/dm2 with the average of current efficiency is 96%.